A study on the dyeing characteristics and electrochemical behaviour of lawsone-indigo mixtures - Komboonchoo S. (2014)
The dyeing characteristics of lawsone-indigo mixtures on wool and their electrochemical properties were studied as a model for natural dyeing. To determine the optimum conditions for dyeing, experiments with different levels of pH in the oxidising and reducing states were performed. The dyeing characteristics on wool were studied using basic colour measurement. The colour depth of the dyeings was strongly dependent on the pH of the solution. Dyeing of lawsone in oxidising and reducing states at pH4-6 showed the highest colour depth. For lawsone-indigo mixtures, the pH of the maximum colour strength shifted to pH6-7. The dyeing properties of henna showed similar behaviour to the lawsone dyeing. The electrochemical properties of the lawsone-indigo mixtures were studied using cyclic voltammetry. The cathodic peak current increased with the increasing lawsone concentration. Furthermore, the cathodic peak current of the lawsone-indigo mixtures, which was less than the cathodic peak current of pure lawsone, indicates the sorption of lawsone molecules on the surface of dispersed indigo. © 2011 The Authors. Coloration Technology © 2011 Society of Dyers and Colourists.